Sector Wise Stock Market Performance during Pre and Post Covid Era - Dr. Avijit Sikdar (International Journal of Engineering and Management Research, 2021)
The spread of the Covid-19 pandemic has an unprecedented and immense impact on the world economy as well as the Indian economy. The stock market, treated as a barometer of the economic activity of any country is adversely affected. Not even in India, countries like Germany, France, the USA, and Spain have been strongly affected. Nationwide lockdown, restriction on the transportation system, demand-supply disequilibrium lead to slow down in the economy and create a fear factor among the participants of the capital market. Rapid fall in the share price and increased volatility are identified during this period. The present study tries to compare the stock price return volatility, no of the transaction, and delivery percentage of various listed companies listed on BSE during the pre and post COVID 19 periods to examine the effect of this pandemic on the economy as a whole. Period of Study: In this paper, we have consideredthe pre-covid period from 1st September 2019 to 15th March 2020 and post covid period from 16th March 2020 to August 2020. Sample: for this study, we have selected 50 BSE listed Companies covering 5 sectors, viz. Pharma, Automobile, Industrial Products, Banking and Finance, and Consumer Goods. Statistical Method: We have used paired sample t-test for comparing the arithmetical mean of different capital market parameters for these two sub-periods for each sector separately and standard deviation of daily return as a measure of volatility. Conclusion: From the study, we have observed that average daily share price; average daily return; daily no. of transactions and volatility is significantly different from pre and post covid period for most of the sectors. However, we have not perceived any significant difference in the delivery percentage of traded shares of these sectors between two study periods.